Antibacterial Effectiveness Test of Roselle Flower (Hibiscus sabdariffa L.) Ethanol Extract Against Escherichia coli, Staphylococcus aureus, and Propionibacterium acnes Bacteria - Nababan, Febryanti; Panjaitan, Ivonne M. S.; Ricky, Donn Richard (Jurnal Biologi Tropis, 2025)
Bacterial infections are a growing global health challenge, especially with the increasing cases of antibiotic resistance. This study used a true experimental method with a posttest-only control group design to investigate the antibacterial efficacy of roselle flower (Hibiscus sabdariffa L.) ethanol extract against the bacteria Staphylococcus aureus, Escherichia coli, and Propionibacterium acnes. The maceration method was used to extract the roselle flowers using 70% ethanol as the solvent, and the disc diffusion method was used to test for antibacterial activity at extract concentrations of 30%, 40%, and 50%, using the antibiotic chloramphenicol as a positive control. The results showed that the roselle flower ethanol extract exhibited antibacterial activity against all three test bacteria. The highest inhibition zone against E. coli was found at 50% concentration (9.87 mm), classified as moderate. For S. aureus, the 50% concentration produced the highest inhibition zone (18.13 mm) with strong classification, while 30% and 40% concentrations also demonstrated strong inhibitory effects. For P. acnes, all extract concentrations showed strong inhibitory responses with the highest inhibition zone at 50% concentration. Chloramphenicol antibiotic consistently demonstrated higher antibacterial activity across all test bacteria. Statistical analysis revealed significant differences in inhibitory effectiveness based on extract concentration and bacterial type (p<0.001), with a significant interaction between these two factors (η²=0.605). These findings indicate the potential development of roselle flower ethanol extract as a natural antibacterial agent, although further optimization is needed to enhance its effectiveness.